2017
DOI: 10.1155/2017/7087086
|View full text |Cite
|
Sign up to set email alerts
|

Direct Assessment of Wall Shear Stress by Signal Intensity Gradient from Time-of-Flight Magnetic Resonance Angiography

Abstract: The aim of the study was to calculate the arterial wall signal intensity gradient (SIG) from time-of-flight MR angiography (TOF-MRA) and represent arterial wall shear stress. We developed a new algorithm that uses signal intensity (SI) of a TOF-MRA to directly calculate the signal intensity gradient (SIG). The results from our phantom study showed that the TOF-MRA SIG could be used to distinguish the magnitude of blood flow rate as high (mean SIG ± SD, 2.2 ± 0.4 SI/mm for 12.5 ± 2.3 L/min) and low (0.9 ± 0.3 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…With a workflow that takes less than 5 min, the present study suggests that TOF-MRA SIG could provide specific hemodynamic information for each subject. Thus, it can help clinicians make rapid decisions by offering an effective screening process regarding the risk of cardiovascular disease for a patient and in deciding whether or not further examination is required [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With a workflow that takes less than 5 min, the present study suggests that TOF-MRA SIG could provide specific hemodynamic information for each subject. Thus, it can help clinicians make rapid decisions by offering an effective screening process regarding the risk of cardiovascular disease for a patient and in deciding whether or not further examination is required [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…4D flow MRI, which is based on dynamic phase display of the flow, can provide the arterial WSS distribution [ 7 ], but previous studies have reported that it is not appropriate for analyzing arterial WSS [ 29 , 39 ]. In clinical practice, the use of 4D flow MRI for estimating WSS remains limited due to the unclear relevance of WSS and concerns about its accuracy due to poor spatial resolution along the arterial wall [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, carotid artery endothelial signal intensity gradient (SIG) from time-of-flight magnetic resonance angiography (TOF-MRA) was reported to represent the relative ESS, showing strong positive correlations with wall shear stress from computational fluid dynamics [11]. TOF-MRA, which is based on the physiologic feature of flow enhancement in the construction of vascular imaging, is one of the most commonly used angiographies [12,13].…”
Section: Introductionmentioning
confidence: 99%